Student’s Perceptions of Differentiated Learning in EFL Classroom - Kamila, Bintana Cahya; Rakhmawati, Rakhmawati; Kurniawati, Bachrijah (International Journal of English Education and Linguistics (IJoEEL), 2025)
This study investigates students’ perceptions of differentiated learning in an English as a Foreign Language (EFL) classroom, emphasizing four key dimensions: acceptance of differentiated learning, instructional strategies, learning environment, and learning outcomes. The research was conducted with 35 students from class XI-E at SMAN 10 Surabaya, who responded to a questionnaire designed to measure their experiences and attitudes toward differentiated instruction. The findings reveal that students generally expressed positive responses to the implementation of differentiated learning. They agreed that the classroom environment and teaching approaches were supportive of their individual preferences and meeting the learning outcomes, particularly when activities were tailored to visual, auditory, and kinesthetic (VAK) learning styles. This indicates that differentiated learning has the potential to foster inclusivity by addressing diverse needs within the same classroom. Although all four dimensions received average to high scores, instructional strategies were rated somewhat lower compared to other aspects, highlighting the necessity for further refinement in the delivery of differentiated methods. The results suggest that, while differentiated learning can create a more engaging and meaningful experience for students, its success depends on the teacher advanced skills in implementing the method and development while also the active involvement of the student itself. Overall, the study underscores differentiated learning as a promising approach in enhancing EFL learning.